What is "prison culture"?: developing a theoretical and methodological foundation for understanding cultural schema in prison - Young, Jacob T. N. (Criminology, 2023)
What does it mean to say that a prison has a "culture?" Scholars have long emphasized the presence of a "prison code" and, more recently, a "racial code" as salient cultural domains in men's prisons. Yet, even though most people intuitively understand what is meant by "prison culture," little progress has been made regarding the conceptualization and operationalization of culture as an analytical construct in prison scholarship. The current study makes two primary contributions to this literature. First, drawing on advances in anthropology, cultural sociology, and cognitive science, we incorporate the concept of cultural schema to provide a concrete analytical construct. Second, we test varying conceptualizations of cultural schema as either characterized by consensus or as overlapping relational structures. Using cultural consensus and correlational class analyses among a sample of 266 incarcerated men, we find little evidence of a culture of consensus for either the prison code or the racial code. Furthermore, we show evidence of heterogenous schema among these cultural domains. Our study is relevant to wider disciplinary work on culture as the problem of analytical precision we address is characteristic of much of the work in criminology and criminal justice that evokes culture as an explanatory device.